Eskalasi Efektivitas Pemasaran Media Sosial: Dampak Konten Iklan TikTok dan Perilaku Konsumen terhadap Pembelian Produk Fashion di Platform Shopee - Kahfiansyah, Muh. Ade; Juanna, Andi; Kusuma, Citra Aditya (MES Management Journal, 2024)
Social media marketing has gained popularity for its ease of access in promoting products. With platforms like TikTok, the social media marketing is proving effective in reaching and influencing target customers. This study aimed to examine the impact of advertising content and consumer behavior on the purchasing of fashion products on the Shopee platform. Employing causal associative quantitative methods, this research sought to explain the cause-and-effect relationships among the variables. The sample was selected through purposive sampling, with respondents invited to complete an online questionnaire via Google Forms. Data analysis was conducted using causal associative quantitative methods and the SPSS 26 software. The results indicated that TikTok advertisement content and consumer behavior simultaneously had a positive and significant impact on the purchase of fashion products on Shopee. These two independent variables accounted for 60% of the variation in fashion product purchases on Shopee, with the remaining 40% attributable to other unexamined factors.